Sports Kinesiology: Concepts and Applications in Improving the Physical and Mental Health of Athletes - Asri Awal (Journal Physical Health Recreation (JPHR), 2025)
This study aims to analyze the concept and application of sports kinesiology in improving athletes’ physical and mental health through a multidisciplinary approach encompassing biomechanics, physiology, neuromuscular control, and sports psychology. The research employs a descriptive literature review method by examining scientific studies published between 2020 and 2025. Findings indicate that the application of kinesiological principles significantly enhances muscle strength, movement efficiency, postural balance, and reduces injury risk. Moreover, kinesiology-based interventions contribute to improved emotional regulation, self-confidence, and athletes’ psychological well-being. The integration of technologies such as wearable sensors, 3D motion capture, and AI-based biomechanical modeling further strengthens kinesiology’s effectiveness in monitoring and personalizing training programs. Therefore, sports kinesiology serves as an essential scientific foundation for developing training systems that focus not only on performance but also on holistic physical and mental health balance in athletes.